EFEKTIVITAS PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) DAN DAMPAKNYA TERHADAP PENDAPATAN KELUARGA - Ni Kadek Ari Sintya Dewi (STIMI Handayani Denpasar, 2019)
The poverty is one of the problems that has become attention center of the government in any country. Bali government has been pursuing programs to alleviate poverty, one of them is Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS). East Denpasar Subdistrict, Denpasar City is one of the regions that has implemented UPPKS program with the largest number of program participants in Denpasar City. The purpose of this study is to determine UPPKS program’s effectiveness level and its impact on family income in East Denpasar Subdistrict, Denpasar City. Program’s effectiveness is measured by input variables, process variables, and output variables. Input variables include: program socialization, assistance accuracition as needed, assistance punctuality, assistance amount accuracition, targets accuracition and returning assistance punctuality. Process variables include mentoring and evaluation / monitoring, while the output variable is participants program income. The analytical tool used in this study is descriptive statistics to determine the program’s effectiveness and statistical analysis, namely the different test of the average pairing observation to determine the program’s role in increasing income. The results of the analysis show that UPPKS program in East Denpasar Subdistrict, Denpasar City is very effective and the program’s role in increasing income is significant at alpha 5 percent.